1998
DOI: 10.1046/j.1523-1747.1998.00184.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphedematous Skin and Subcutis: In Vivo High Resolution Magnetic Resonance Imaging Evaluation

Abstract: Physico-chemical and morphologic parameters of skin layers and subcutaneous tissue in lymphedematous limb were studied in vivo using magnetic resonance imaging. High resolution images were obtained with a depth resolution of about 70 microm, using a specific surface gradient coil specially designed for skin imaging and connected to a standard whole-body imager at 1.5 T. Twenty-one patients with unilateral lower extremity lymphedema (11 primary and 10 secondary) were examined. Skin thickness, relaxation times, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 35 publications
0
32
0
3
Order By: Relevance
“…A variety of techniques has been investigated for the noninvasive measurement of epidermal thickness emphasizing the high demand for a suitable method. However, techniques such as optical coherence tomography [15,16], NIR reflectance confocal microscopy, high-frequency ultrasound imaging [17,18], high-resolution magnetic resonance imaging [19] and pulsed terahertz radiation [20] do not achieve a sufficient resolution to measure the SC thickness other than at the heel or palm. A higher resolution is achieved with confocal microscopy methods.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of techniques has been investigated for the noninvasive measurement of epidermal thickness emphasizing the high demand for a suitable method. However, techniques such as optical coherence tomography [15,16], NIR reflectance confocal microscopy, high-frequency ultrasound imaging [17,18], high-resolution magnetic resonance imaging [19] and pulsed terahertz radiation [20] do not achieve a sufficient resolution to measure the SC thickness other than at the heel or palm. A higher resolution is achieved with confocal microscopy methods.…”
Section: Resultsmentioning
confidence: 99%
“…23 The T 2 values determined here, on the order of 64 ms in the healthy gum, are longer than those found in normal (36 ± 4 ms) or oedematous (40 ± 8 ms) skin dermis. 21 Lymphoedema was found to significantly increase the T 2 value found in the dermis, but to a smaller extent in the epidermis. Gingivitis is characterized by gingival bleeding and signs of gingival inflammation.…”
Section: Discussionmentioning
confidence: 85%
“…Because the thickness of the skin is small, MRI of the skin demands high resolution and high sensitivity. Recent developments in surface coil technology and high field scanners have made MRI useful to study superficial skin structures at high resolution (Idy-Peretti et al, 1998;Richard et al, 1991). Bond et al (1991) analyzed choroidal melanoma by MRI technique at various stages like pre-and postoperation.…”
mentioning
confidence: 99%
“…The in vivo MRI in medical diagnosis has been reported to differentially evaluate malignant melanoma tumors (Maurer et al, 2000) and subcutaneous and pigmented skin of nodular and superficial spreading melanoma (Schwinghofer et al, 1989). Idy-Peretti et al (1998) have reported application of MRI for evaluating lymphodema in skin layers and subcutaneous tissue. An attempt has been made to evaluate unusual or aggressive tumors (eg, verrucous and sebaceous carcinoma) using MRI (Zemtsov et al, 1992a).…”
mentioning
confidence: 99%